Hotspotters Project: a study protocol for a stepped wedge cluster RCT on the cost-effectiveness of 12-month proactive, integrated and personalised care for patients with problems on multiple life domains and high acute care use - Mattijs E Numans; Marc Abraham Bruijnzeels; Rimke C Vos; Elske M van den Akker-van Marle; Mark van der Wel; Vera Tiemes; Kimberley A Leming; Hanneke Borgdorff; Laurens C van Gestel; Marieke A Adriaanse (BMJ Open)
Introduction ‘Hotspotters’ are patients with complex care needs, defined by problems in multiple life domains and high acute care use. These patients often receive mismatched care, resulting in overuse of care and increased healthcare costs. As reliable data on effective interventions for this population are scarce, the goal of this study is to assess the cost-effectiveness of proactive, personalised, integrated care for this group.Methods and analysis The Hotspotters Project is planned as a stepped wedge cluster randomised controlled trial in 20 primary care practices in the Netherlands. All practices and participants will begin with standard care during the control period (2–8 months), followed by an intervention (12 months) consisting of a positive health intake with goal setting, multidisciplinary meetings, a personalised care plan and proactive care management. The study will conclude with a follow-up (2–8 months), resulting in a total study duration of 22 months. We plan to include 200 patients with (a) problems on two or more life domains and (b) at least two acute care encounters in the previous year. Possible Hotspotters are identified using an Adjusted Clinical Groups-based algorithm or via a local primary healthcare team.Outcomes Questionnaires and routine care data will be used to gather data on cost-effectiveness, which will then be assessed using multilevel analysis, with levels for the individual, cluster and duration of control period. Secondary outcomes will include psychological outcomes on self-regulation (proactive coping, patient activation, self-efficacy and intention), experience of care (satisfaction, perceived autonomy support and qualitative data from focus groups) and quality of life, qualitative analysis of the Positive Health approach, implementation outcomes and process evaluation including integration of care.Ethics and dissemination The Ethics Committee of Leiden University Medical Centre granted approval (METC-LDD, P21.123). Results will be shared through peer-reviewed publication and (inter)national conference presentations.Trial registration number NCT05878054.